Concepts of Ethics in Applied Linguistics Research - Egido, Alex (2020)
Ethics in research has drawn attention of applied linguists in the past years. Such consideration has created room to both theoretical propositions and practical actions. This article aims at arguing that the adoption and discussion of ethics in research is not solely related to physical or intentional harm and at recommending that applied linguists reflect on the ethical dimension(s) of their studies, as well as incorporate those reflections on their research reports. In order to achieve those goals, theoretical propositions are discussed and illustrated in terms of traditional and emergent ethics dimensions.